2005
DOI: 10.1590/s0100-204x2005001200006
|View full text |Cite
|
Sign up to set email alerts
|

Pollination efficiency of the stingless bee Melipona subnitida on greenhouse sweet pepper

Abstract: -The present study was carried out in Northeastern Region of Brazil, in order to investigate the use of stingless bee Melipona subnitida Ducke in the pollination of greenhouse sweet pepper (Capsicum annuum L.). Treatments of hand cross-pollination, hand self-pollination, pollination by bees and restricted pollination were performed. Results showed that despite sweet pepper flowers are considered autogamous, this crop benefits from pollination by M. subnitida, producing fruits significantly heavier and wider, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 9 publications
2
36
1
12
Order By: Relevance
“…Os resultados aqui verificados sugerem que a autopolinização garante a formação de sementes no pimentão e posteriores visitas de insetos (sem especificidade) às flores maximiza esta produção (SHIPP et al, 1994;JARLAN et al, 1997;CRUZ et al, 2005). Tabela 1.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Os resultados aqui verificados sugerem que a autopolinização garante a formação de sementes no pimentão e posteriores visitas de insetos (sem especificidade) às flores maximiza esta produção (SHIPP et al, 1994;JARLAN et al, 1997;CRUZ et al, 2005). Tabela 1.…”
Section: Resultsunclassified
“…Tabela 1. Médias + desvios-padrão dos parâmetros "massa do fruto" (PF), "comprimento do fruto" (CF), "diâmetro do fruto" (DF), "espessura do pericarpo" (EP) e "número de sementes/ fruto" (NS) de frutos de pimentão produzidos nos tratamentos "parcelas livremente visitadas", "parcelas isoladas de insetos" e "parcelas com uma colméia de Apis mellifera" (KRISTJANSSON e RASMUSSEN, 1991;DE RUIJTER et al, 1991;SHIPP et al, 1994;JARLAN et al, 1997;DAG e KAMMER, 2001;CRUZ et al, 2005). O impacto positivo da polinização entomófila em DF corrobora os resultados anteriormente obtidos (SHIPP et al, 1994;CRUZ et al, 2005) e, com relação à variável EP, nenhum outro autor avaliou este parâmetro, embora seja um dos principais atributos de qualidade dos frutos de C. annuum MELO (1997).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Although these species are classified as autogamous, some genotypes present allogamy rate which ranges from 2 to 90% (BOSLAND & VOTAVA, 2000), and some studies show benefits of pollinators presence (CRUZ et al, 2005;SERRANO & GUERRA-SANZ, 2006;NASCIMENTO et al, 2012).…”
Section: Objetivou-se Verificar O Efeito Da Vibração De Plantas Na Prmentioning
confidence: 99%
“…For sweet pepper, CRUZ et al (2005) reported the influence of stingless bee Melipona subnitida in order to pollinate, contributing to the production of heavier fruits, with higher diameter, greater number of seeds and lower percentage of malformed fruits when compared to self-pollinated crops. The authors believe that the presence of these insects contribute to greater pollen supply, increasing the number of embryos and favoring the fruit development.…”
Section: Objetivou-se Verificar O Efeito Da Vibração De Plantas Na Prmentioning
confidence: 99%